INVESTMENT DECISION, PROFITABILITY AND OTHER FACTORS AFFECTING FIRM VALUE - Setiawan, Alvin Buddhi; Prajitno, Sugiarto (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
This research was conducted with the aim of providing empirical evidence that corporate social responsibility, along with other factors such as institutional ownership, dividend policy, investment decision, earnings, leverage, and profitability have an impact on firm value. The study used multiple linear regression and was processed using statistical package. The data used in the research from cyclical and non – cyclical companies that consistenty been listed in indonesia Stock Exchanges for the 2020-2022 period with a research period of 2020-2022. The results of this research indicate that investment decision and profitability have positive impact a significant on firm value and dividend policy have negative impact on firm value. Meanwhile, variable institutional ownership, corporate social responsibility, leverage and earnings don’t have a significant impact on firm value.